Musculoskeletal Injury Profile of Acrobatic Gymnasts: an International Study - Francisca Teixeira da Costa Maia (2022)
Acrobatic gymnastics (ACRO) is increasing in popularity worldwide. Since its Olympic debut at the Summer Youth Olympic Games (2018), fans are eagerly waiting for its entrance at the Olympics. Despite its high physical demands, there is a knowledge gap on ACRO related injuries. We designed a cross-sectional survey to evaluate the incidence, anatomic distribution and type of acute and overuse injuries, and discuss preventive measures. With this aim, gymnasts were recruited worldwide through direct contact or contact with clubs and federations, by email, social media, and word of mouth communication. The questionnaire was completed by 480 gymnasts from various competitive levels, including national team gymnasts and European and World champions. It was found that the majority of acrobats (76.3%) had sustained an injury in the past 24 months, with an overall incidence rate of 1.5 injuries per 1000 hours of exposure, and bases being more injured than tops. For acute injuries, the ankle was the most affected body area, with fractures and ligament sprains being the most common injury types. From these, 53.2% were time-loss injuries, with a mean suspension time of 6.8 weeks. For overuse injuries, lumbosacral spine and tendinopathy were the most frequent body area and injury type, respectively. From these, 28.3% were time loss injuries, with a mean suspension time of 9.1 weeks. This is the first international and the largest study on ACRO related injuries, providing the basis for developing targeted and potentially more effective preventive measures.